AI Systems and Respect for Human Autonomy - Laitinen, Arto; Sahlgren, Otto (Frontiers in Artificial Intelligence, 2021)
This paper concerns the sociotechnical bases of human autonomy. Drawing on recent literature on AI ethics, philosophical literature on dimensions of autonomy, and on independent philosophical scrutiny, we first propose a multi-dimensional model of human autonomy and then discuss how AI systems can support or hinder human autonomy. What emerges is a philosophically motivated picture of autonomy and of the normative requirements personal autonomy poses in the context of algorithmic systems. Ranging from consent to data collection and processing, to computational tasks and interface design, to institutional and societal considerations, various aspects related to sociotechnical systems must be accounted for in order to get the full picture of potential effects of AI systems on human autonomy. It is clear how human agents can, for example via coercion or manipulation, hinder each other’s autonomy, or how they can respect each other’s autonomy. AI systems can promote or hinder human autonomy, but can they literally respect or disrespect a person’s autonomy? We argue for a philosophical view according to which AI systems – while not moral agents or bearers of duties, and unable to literally respect or disrespect – are governed by so-called ought-to-be norms. This explains the normativity at stake with AI systems. The responsible people (designers, users etc.) have duties and ought-to-do norms, which correspond to these ought-to-be norms.